Religious Status of Using Assisted Reproductive Technologies in Human Reproduction - MG Jafarzadeh (JRI, 2000)
Introduction: To draw a general picture of the current Iranian-law and Shiah Fiqh position as to the Assisted Reproduction: -whether allowed or not, - and, to show how and what changes could occur in this field. Materials and Methods: Examination of the Iranian legislation and judicial decisions, consideration of jurisprudential verdicts of the eminent Shiah jurists and interpretation of the original sources of Shiah-Islamic law: Quran and Tradition of the Prophet of Islam and Twelve Shiah Imams, by the method of ljtehad. Results: 1- Lack of clear and comprehensive legislation and guiding judicial decisions: no obvious enactment exists to determine whether or not the ART specialists and Medical centres are allowed to apply these techniques where sperm, egg and fertilized egg donation are concerned, 2- existence of different opinions between the authoritative religious jurists in permitting the use of these techniques, and 3- emergence of extensive divergence between the jurisprudential scholars in interpreting the original sources of the jurisprudence (Fiqh) which would naturally affect the legislative authority and the courts when dealing with the case. Conclusion: These results show that the position of the Iranian law is currently complicated, at least, where the case of sperm, egg and embryo donation is concerned and it is feared that the courts might decide differently if a case of such kind arise before them. This suggests that the Iranian authorities should interfere in this area of the law to provide a new legislation. Examination of the verdicts published by the current eminent Shiah jurists show that some cases, such as egg and fertilized egg donation, could be allowed religiously, although the sperm donation is somewhat complicated. However, it is suggested that the authorized authorities are to consider legal problems and social reflections arising out of using donated sperm, egg and fertilized egg when allowing these techniques.